Bioorthogonal Non-canonical Amino Acid Tagging Combined With Flow Cytometry for Determination of Activity in Aquatic Microorganisms - Lindivat, Mathilde; Larsen, Aud; Hess-Erga, Ole Kristian; Bratbak, Gunnar; Hoell, Ingunn Alne (Frontiers in Microbiology, 2020)
In this study, we have combined bioorthogonal non-canonical amino acid tagging (BONCAT) and flow cytometry analysis (FCM), and demonstrate the applicability of the method for marine prokaryotes. Enumeration of active marine bacteria was performed by combining the DNA stain SYBR Green with detection of protein production with BONCAT. After optimization of incubation condition and substrate concentration on monoculture of E. coli, we applied and modified the method to natural marine samples. We found that between 10 and 30% of prokaryotes in natural communities were active. The method is replicable, fast, and allow high sample throughput when using FCM. We conclude that the combination of BONCAT and FCM is an alternative to current methods for quantifying active populations in aquatic environments.